Islamic Finance in Africa: An Analysis Using Bibliometrix R-Tool - Adam, Muniem (SMART Insight, 2024)
Islamic finance in Africa is a growing sector, offering financial services that adhere to Islamic principles (Shariah), including the prohibition of interest (riba) and speculative activities (gharar). This industry plays an essential role in addressing the continent's development challenges by providing innovative financial solutions that promote economic inclusiveness and ethical practices. This study quantitatively analyzes the literature on Islamic finance in Africa spanning from 1992 to 2024 using articles indexed in Scopus. It adopts a combination of bibliometric and content analysis approaches. The findings indicate Hasan M. Kabir as the most prominent author, the United Kingdom with the most relevant quantity of authors, and Africa as the prevailing keyword. Addressing the absence of prior bibliometric studies, this inaugural research covers: (1) Islamic finance and African development (2) Islamic banking drives investment in Africa and (3) Islamic finance in East Africa.